(untitled) (Vietnam Journal of Community Medicine, 2023)
Background: A cross-sectional study was conducted on 369 full-time health sciences students studying at Phenikaa University to find out about the status and some factors related to the signs of anxiety, depression, and stress among students during the COVID-19 pandemic. Results: The prevalence of students with anxiety, depression, and stress was (11.1%), (11.1%) and (4.9%) respectively. Factors, such as male gender and history of psychological problems (psychological stress, anxiety disorders, depression, sleep disturbances), were identified to affect the psychology of female students during the COVID-19 pandemic. Conclusion: The percentage of students showing signs of anxiety, depression, and stress is relatively high in this study, indicating the support plans and extracurricular programs from school to help students release and balance their psychological health to improve the above situation.